On the non-uniqueness of the solution to a boundary value problem of heat conduction with a load in the form of a fractional derivative - Kosmakova, M.T.; Izhanova, K.A.; Khamzeyeva, A.N. (Bulletin of the Karaganda University. Mathematics Series, 2022)
The paper deals with the second boundary value problem for the loaded heat equation in the first quadrant. The loaded term contains a fractional derivative in the Caputo sense of an order α, 2 < α < 3. The boundary value problem is reduced to an integro-differential equation with a difference kernel by inverting the differential part. It is proved that a homogeneous integro-differential equation has at least one non-zero solution. It is shown that the solution of the homogeneous boundary value problem corresponding to the original boundary value problem is not unique, and the load acts as a strong perturbation of the boundary value problem.